The intersection of film, teaching, and inclusive education - Restianty, Ajani; Khang, Nguyen Tan; Mahameruaji, Jimi Narotama (ProTVF, 2024)
Background: The convergence of film, teaching, and inclusive education research on education has received much attention recently because it can potentially improve educational experiences and create social change. Purpose: This intersection of disciplines provides educators an immense tool for engaging children, cultivating empathy, and addressing social and cultural inequities. Using film's emotional connection and narrative force, educators may build more diverse and efficient learning environments that meet the different needs of their students. Methods: This study used existing data from Scopus to analyze the intersection of film, teaching, and inclusive education using bibliometric quantitative publications studies to assess academic influence. It entails analyzing citations, publication trends, and other bibliographic information. Results: The findings underline the importance of utilizing films to encourage inclusive school practices. Films can reduce socioeconomic inequities, raise cultural knowledge, and improve inclusive teaching techniques. This study underlines the relevance of using film in instructional approaches to promote inclusive education practices and increase learning results. Films are exhibited to promote critical thinking about teaching methods, interpersonal relationships, and classroom ethics. Conclusion: Introducing film into teaching techniques can boost student engagement, improve critical thinking abilities, and raise cultural understanding. Subsequently, this bibliometric study provides a helpful overview of the present research environment in films, teaching, and inclusive education, serving as a foundation for academics to investigate and introduce new modern topics from various regional and cultural perspectives. Implications: Future research should examine the confluence of films, teaching, and inclusive education, as well as the ramifications of these encounters for educational settings, and compare them across study areas and locations or other relevant scopes.